(untitled) (Вестник КазНУ. Серия Востоковедения, 2016)
In the article the peculiarities of polite nesses genre are being determined and cleared up its place in the Arabic literature. On the basing on valuable ideas of the oriental scientists are being informed about of polite nesses genre.